Pengaruh Mutu Pelayanan Dokter Terhadap Loyalitas Pasien di RS PKU Muhammadiyah Bantul - Tati Fatmawati; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
Doctors is one of the main resources that provide services directly to patients. Doctor’s quality service at the hospital will build the patient’s attitudes and trust related to the reuse of hospital services. Loyal patients will have linkages with hospital and enable the ralization of long term relationship. Purpose knowing the influence of technical skills, interpersonal relationship, availability of information and the involvement of patient to the patient loyalty at general polyclinic in RS PKU Muhammadiyah Bantul. This research is an analytic inferential with cross sectional approaches. Populations of this research are olden patient in general polyclinic at RS PKU Muhammadiyah Bantul. Sampling technique is purposive sampling with number of samples are 87 persons. Collecting data using kuesioner. Data analysis with multiple regretion analysis. There is influence doctor quality service to the patient loyalty. Dimentions who influence to the patient loyalty are technical skill, interpersonal relationship, availability of information, and patent involvement. All dimensions of doctor quality service include technical skills, interpersonal relationship, and availability of information and the involvement influence of patient to the patient loyalty. Technical skills, interpersonal relationship, availability of information, and patent involvement have an influence to the patient loyalty in general polyclinic in RS PKU Muhammadiyah Bantul.